Changes in regional body composition explain increases in energy expenditure in elite junior basketball players over the season - Silva, A. M.; Santos, D. A.; Matias, C. N.; Roch, P. M.; Petroski, E. L.; Minderico, C. S.; Sardinha, L. B. (European Journal of Applied Physiology, 2012)
We aimed to analyze the association between changes in total and regional fat (FM) and fat-free mass (FFM) over a season with resting (REE) and total energy expenditure (TEE) in elite basketball players. At the beginning of the pre-season and at the final of the competitive period, measures of total and regional FM, FFM, lean soft tissue (LST), and bone mineral estimated by DXA and REE by indirect calorimetry were obtained in eight males and nine females of the Portuguese basketball team (16-17 years). TEE was assessed by doubly labeled water. Handgrip and a vertical-jumping were used to assess strength and power. Changes were expressed as a percentage from the baseline values. Resting energy expenditure and TEE increased by 13.2 ± 12.6 and 13.3 ± 12.7% (p < 0.01), respectively. Increases in FFM (3.6 ± 2.2%) and reductions in relative FM (-4.0 ± 6.6%) were observed (p < 0.01). The strength and power increased by 14.4 ± 9.9 and 9.8 ± 10.6%, respectively (p < 0.001). Alone, FFM and arms LST differences explained 25 and 23% of the total variance in REE alteration. These variables remained associated after adjusting for gender and baseline values (ß = 0.536, p = 0.042; and ß = 2.023, p = 0.016, respectively). Over the season, the REE increase was explained by changes in FFM. The increase in REE along with the strength and power improvement may suggest that a qualitative change in the metabolic active tissues occurred. Furthermore, these findings highlight the regional LST contribution, specifically located at the upper limbs, as a key component for the higher REE occurred over the season in junior basketball players.